Comprehensive reaction kinetics model of CO2 absorption into 1‐dimethylamino‐2‐propanol solution. Issue 11 (6th July 2022) - Liu, Helei; Jiang, Xiaotong; Idem, Raphael; Dong, Shoulong; Tontiwachwuthikul, Paitoon
Abstract: In the present work, the kinetics of the reactive absorption of CO2 in 1‐dimethylamino‐2‐propanol (1DMA2P) solution were experimentally measured using a laminar jet absorber over a temperature range of 298–313 K, 1DMA2P concentration range of 0.5–2.0 mol/L, and CO2 loading range of 0–0.06 mol CO2 /mol amine. The measured kinetics data were then used to develop a comprehensive numerical kinetics model using a FEM‐based COMSOL software. The reaction rate model of the CO2 absorption into 1DMA2P solution were then validated by comparing model rates with the experimental rates. An excellent agreement of model data with experimental data was achieved with an absolute average deviation (AAD) of 6.5%. In addition, vapor–liquid equilibrium plots of all ions in the 1DMA2P‐H2 O‐CO2 system were also developed. Further, this work has provided an effective criterion for evaluating CO2 absorption, that can be used for both the conventional amines and alternative amines for the purpose of providing guidelines or information on how to effectively screen solvents.